Improving seed germination in forage legumes for propagation and agronomic trials - Madera Doria, Yaira; Cardoso, Juan Andres; Madera Doria, Pascual (2025)
Improving germination speed and uniformity is essential to ensure robust trial establishment. The described germination protocol was developed specifically to overcome physical dormancy in forage legume seeds and to standardize germination outcomes. Through controlled scarification and optimized hydration and environmental conditions, the protocol reduces germination time to 2–10 days and achieves 80–90% germination rates, representing a substantial improvement over standard practices.